PENGARUH KOMPETENSI MANAJERIAL DAN GAYA KEPEMIMPINAN TERHADAP KEINOVATIFAN PEJABAT ADMINISTRATOR DI PROVINSI JAMBI - Enadarlita, Enadarlita (Graduate Program Magister Manajemen Pendidikan, 2019)
This study aims to analyze the effect of managerial competence and leadership style on the innovativeness of administrator officials in Jambi Province both partially and simultaneously. Using quantitative methods, with data collection techniques in the form of interviews, observation, questionnaires, and documentation. The conclusions that can be drawn from this study are: (1) there is an influence between managerial competencies on the innovativeness of administrator officials, with managerial competency coefficients (X1) on innovativeness (Y) or Ï1 of 0.273 with t count 3.960 and Sig 0,000 t table 1, 67, so t count> t table (3.960> 1.67), meaning Ho is rejected and Ha is accepted; (2). There is the influence of leadership style on innovativeness, with the results of the leadership style coefficient (X2) on innovativeness (Y) or Ïy2 of 0.650 with t count of 9,442 and Sig 0,000 t table 1.66, so t count> t table (9,442> 1,66) , means that Ho is rejected and Ha is accepted; (3) There is a positive influence jointly managerial competency variable (X1) and leadership style (X2) on innovation (Y), by comparing the probability value (sig) of the calculation results with a significant level <0.05. Regression Test results obtained Fcount 127.201> Ftable 3.94 with probability values (sig) 0,000b <0.05 means managerial competence (X1) and leadership style (X2) together have a positive effect on innovation (Y) with significant results.